Comparative and correlative levels of copper, zinc, with ceruloplasmin and metallothionein in art-HIV infected and non-art-HIV infected subjects: A cross-sectional study. - Rao T, Nageswara; A.Srinivas; Dr .Manju Thomas; Dr. Yakaiah Vangoori; Sayana, Dr. Suresh Babu (Student's Journal of Health Research Africa, 2025)
Background: Trace elements such as copper and zinc, along with their transport proteins ceruloplasmin and metallothionein, play crucial roles in immune function and oxidative balance. Human immunodeficiency virus (HIV) infection and antiretroviral therapy (ART) alter these micronutrient levels, influencing disease progression and metabolic complications. Objectives: To compare and correlate copper, zinc, ceruloplasmin, and metallothionein levels between ART-HIV–infected and non-ART-HIV–infected subjects and evaluate associated biochemical and metabolic parameters. Methods: A cross-sectional study was conducted on 200 HIV-infected subjects (100 on ART, 100 not on ART) attending a tertiary care center. Demographic, physical, lipid, glycaemic, and trace element parameters were assessed using standard biochemical methods. Statistical analysis was performed with SPSS software; p < 0.05 was considered significant. Results: The mean age of participants was 55.5 ± 6.2 years, with a male-to-female ratio of 1.3:1. BMI was significantly higher in ART-HIV subjects (p < 0.0001), while blood pressure and age were comparable between groups. ART-HIV subjects exhibited lower total cholesterol and LDL but higher HDL compared with non-ART-HIV patients. Fasting blood sugar was significantly lower in the ART group (p < 0.001), though insulin levels showed no difference. Notably, serum zinc levels were markedly reduced in ART-HIV subjects (p < 0.0001), whereas copper, ceruloplasmin, and metallothionein were significantly elevated (p < 0.05). A positive correlation was observed between copper and ceruloplasmin, and a negative correlation between zinc and ceruloplasmin. Conclusion: HIV infection and ART significantly alter trace element balance and related biomarkers. ART appears beneficial in improving lipid and glycaemic profiles but is associated with zinc depletion and compensatory increases in copper, ceruloplasmin, and metallothionein. Recommendations: Routine monitoring of trace elements in HIV-infected patients is essential. Zinc supplementation and dietary counseling may mitigate long-term metabolic complications and improve immune resilience.